Identity Management Systems: Singular Identities and Multiple Moral Issues - Ishmaev, Georgy; Stokkink, Quinten (Frontiers in Blockchain, 2020)
The paper looks into some of the competing normative claims surrounding the development of Identity Management systems in general and Self-Sovereign Identity (SSI) systems in particular. It is argued that SSI developments should be assessed against the backdrop of IMs attempting to implement a global identity layer based on aggregated singular identities and reputation scores. It is also argued that this trend defines key ethical issues pertaining to the development of SSI systems. In order to explicate and evaluate these issues, the paper looks at the desirability of singular aggregated identities through the lens of moral-philosophical theories. It is argued that such an analysis strongly suggests moral desirability of a plural identities approach in SSIs that have built-in advantage for the implementation of practical separation of identities.